PENGARUH KOMPETENSI PEDAGOGI GURU TAHFIZ DAN LINGKUNGAN MADRASAH TERHADAP PRESTASI HAFALAN ALQUR’AN SISWA DI MADRASAH TSANAWIYAH NURUL QUR’AN PROBOLINGGO JAWA TIMUR - EE. Junaedi Sastradiharja; Mahmudi Abdillah (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2022)
This study aims to determine and examine data related to the pedagogical competence of tahfidz teachers and the madrasa environment on the achievement of memorizing the Qur'an simultaneously. In this study the authors used a survey method through a questionnaire. The population in this study was 101, then the sample was taken as many as 81 students, using random sampling. The data analysis technique uses descriptive analysis, correlation coefficient, simple regression analysis and multiple regression which are described and described descriptively. The results of this study are: First, there is a positive and significant effect of the pedagogical competence of the tahfidz teacher on the achievement of memorizing the Qur'an based on the results of the partial t test in multiple linear regression analysis. The pedagogical competence of the tahfidz teacher has an effect on students' memorization achievement of 57.0% and the remaining 43.0% is determined by other factors. The simple linear regression equation (unstandardized coefficients B) shows Y = Y = 38.764 + 0.338 X1 which means that every one unit increase in the pedagogical competence score of the tahfidz teacher will have an effect on increasing the student's memorization achievement score of 39,102. Second, there is a positive and significant influence of the madrasa environment on students' memorization achievement based on the results of the partial t test in multiple linear regression analysis. the madrasa environment has an influence on student learning outcomes by 64.2% and the remaining 35.8% is determined by other factors. The simple linear regression equation (unstandardized coefficients B) shows Y = 34.848 + 0.373 X2, which means that each increase in one unit of madrasah environmental score will have an effect on increasing students' memorization achievement scores of 35.221. Third, there is a positive influence on the pedagogical competence of the tahfidz teacher and the madrasa environment simultaneously on the achievement of memorizing madrasas that will have an effect on increasing the score of memorization achievement. based on the results of the simultaneous F test (F test) in multiple linear regression analysis. The magnitude of the influence of the pedagogical competence of the tahfidz teacher and the madrasa environment simultaneously on the achievement of memorization is 73.3% and the remaining 26.7% is determined by other factors. The regression equation (unstandardized coefficients B) shows Y = 28.891 + 0.179 X1 + 0.250 X2, which means that every increase in the pedagogical competence score of the tahfidz teacher and Madrasah environment simultaneously, the student's memorization achievement increases, by 29.320